We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
263
3
avatar

1.

What is (f−g)(x)?

f(x)=x^4−x^2+9

g(x)=x^3+3x^2+12

 

(f−g)(x)= 

 

2. 

What is (f⋅g)(x)?

f(x)=x4−9

g(x)=x3+9

 

(f⋅g)(x)= 

 

Thanks so much!

 Mar 30, 2018
 #1
avatar+7612 
+3

1.

(f - g)(x)   =   f(x) - g(x)

 

(f - g)(x)   =   (x4 - x2 + 9) - (x3 + 3x2 + 12)

 

(f - g)(x)   =   x4 - x2 + 9 - x3 - 3x2 - 12

 

(f - g)(x)   =   x4 - x3 - 4x2 - 3

 

2.

(f ⋅ g)(x)   =   f(x) ⋅ g(x)

 

(f ⋅ g)(x)   =   (x4 - 9) ⋅ (x3 + 9)

 

(f ⋅ g)(x)   =   (x4 - 9)(x3 + 9)

 

(f ⋅ g)(x)   =   (x4)(x3) + (x4)(9) + (-9)(x3) + (-9)(9)

 

(f ⋅ g)(x)   =   x7 + 9x4 - 9x3 - 81

 Mar 30, 2018
edited by hectictar  Mar 30, 2018

9 Online Users

avatar